Leucemia y su incidencia en la salud mental de un adulto mayor de 73 años del cantón Echendia - Estrada Soria, Mary Paola (2022)
The purpose of this research is to determine the mental health condition of a 73-year-old adult with leukemia in the Echeandia Canton, using tools and techniques according to the symptoms exhibited by the patient, therefore, the clinical interview was implemented. , direct observation, complementary tests in order to obtain accurate, reliable results and above all in order to provide support, acceptance, guidance, guidance, accompaniment throughout the process of adult therapy, likewise according to the pertinent inquiry obtained as a result a depressive disorder with a moderate episode, so we worked with Cognitive Behavioral Therapy, which provided us with excellent results such as the modification of thoughts, control, balance of emotions, consistent behavior, encouraging the adult in instrumental activities to reducing isolation, fostering self-esteem, resilience, self-love and acceptance, during the psychological sessions, it was also possible to detect the initial triggering cause of the condition, which is his leukemia disease. All the information obtained helped to complete the questions of his clinical history.